SEASONAL DEVELOPMENT AND HOST PLANT SPECIALIZATION OF EURYDEMA LAPORTE, 1833 (HEMIPTERA: PENTATOMIDAE) (Scientific journal of the Fergana State University, 2024)
This article presents the scientific research results on the development of the Eurydema Laporte, 1833 genus in the conditions of the Fergana Valley and their specialization on host plants. Under the valley's conditions, representatives of this genus can produce up to two generations during the season. E. oleracea feeds on 6 families and 23 species of plants, E. ornata on 1 family and 9 species, E. Fieberi on 4 families and 6 species, E. maracandica on 1 family and 2 species, E. wilkinsi on 1 family and 1 species, E. ventralis on 3 families and 19 species, and E. gebleri on 1 family and 1 species.